Does Demographics Influence Adoption of Information Technology Devices? -an understanding of Rural Consumer Behaviour - Kumari, poonam; Gupta, Nirupma (Journal of Agricultural Extension Management, 2018)
The Information Technology sector has immensely contributed to India’s growth story. It has put India’s name on the global map and has been a major contributor towards the growth of Indian economy. This study assesses the ownership of information technology devices among rural consumers, their preferences towards these devices and whether the demographic characteristics have an impact on ownership and preferences of these devices. Data collection from rural consumers was through a structured questionnaire with questions related to the demographic profile of the respondents, currently available information technology devices and factors responsible for not having them and also related to preferred information technology device. Through the study new information has been generated which is useful in assessing the adoption of information technology devices like laptops, computers, smart-phones, tablets, notebook/netbook etc. by rural consumers. It has been observed that, although the penetration of mobile phones has reached a remarkable number, there is a lot more to be done in order to popularise and increase the demand for other technological devices in rural areas.